“Your Clothes Aren’t Going to Magically Come Off”:An Exploratory Study of U.S. Latino Adolescents’ Reasons for Having or Not Having First-Time Vaginal Intercourse (2014)
US Latino adolescents have higher teenage birthrates and higher probabilities for early sexual initiation, compared to other racial/ethnic groups. Understanding their reasons for delaying or initiating first-time vaginal intercourse is important in designing culturally relevant health promotion programs. Using qualitative methods, we analyzed 21 semi-structured interviews with US Latino adolescents regarding their sexual debuts. Seven had sexually debuted, acknowledging sexual feelings of desire, curiosity and pleasure for their romantic partner. The remaining 14 had not debuted citing reasons of self-interest reasons and external prohibitive factors. Eight out of 14 also attributed their status to not being in a romantic relationship. Our findings suggest several areas for increased discussion including how romantic relationships and Latino cultural values influence sexual initiation and the use of contraception. These findings could improve health promotion programs by identifying critical elements that may resonate with US Latino adolescent socio-cultural values and sexual development.